2014
DOI: 10.1371/journal.pone.0112679
|View full text |Cite
|
Sign up to set email alerts
|

Residual Antibiotics in Decontaminated Human Cardiovascular Tissues Intended for Transplantation and Risk of Falsely Negative Microbiological Analyses

Abstract: We investigated the presence of antibiotics in cryopreserved cardiovascular tissues and cryopreservation media, after tissue decontamination with antibiotic cocktails, and the impact of antibiotic residues on standard tissue bank microbiological analyses. Sixteen cardiovascular tissues were decontaminated with bank-prepared cocktails and cryopreserved by two different tissue banks according to their standard operating procedures. Before and after decontamination, samples underwent microbiological analysis by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 30 publications
2
15
0
1
Order By: Relevance
“…The standard microbiological analysis detected 11 contaminated TISSUE‐C, and three additional TISSUE‐C samples were found contaminated only when the medium was treated with RESEP for elimination of antimicrobial residues before microbiological testing. Although the automated BACTEC system includes resins that partially remove the antimicrobial agents, these findings underlie the importance of total elimination of antimicrobial residues from the tested sample to avoid false negative results, as also confirmed by other recent reports . The identification of the contaminants detected with the RESEP+ method in the cold storage medium, confirmed the same microbial species as those found without RESEP.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The standard microbiological analysis detected 11 contaminated TISSUE‐C, and three additional TISSUE‐C samples were found contaminated only when the medium was treated with RESEP for elimination of antimicrobial residues before microbiological testing. Although the automated BACTEC system includes resins that partially remove the antimicrobial agents, these findings underlie the importance of total elimination of antimicrobial residues from the tested sample to avoid false negative results, as also confirmed by other recent reports . The identification of the contaminants detected with the RESEP+ method in the cold storage medium, confirmed the same microbial species as those found without RESEP.…”
Section: Discussionsupporting
confidence: 83%
“…Although the automated BACTEC system includes resins that partially remove the antimicrobial agents, these findings underlie the importance of total elimination of antimicrobial residues from the tested sample to avoid false negative results, as also confirmed by other recent reports. 21,22 The identification of the contaminants detected with the RESEP+ method in the cold storage medium, confirmed the same microbial species as those found without RESEP.…”
Section: Decontamination Of the Periocular Area And Conjunctival Sac supporting
confidence: 64%
See 1 more Smart Citation
“…Similarly to Buzzi et al , 22 we wanted to verify whether the microbiological positivity observed in the RESEP+ group could have been a consequence of some additional manipulation. However, we excluded this possibility because none of our negative control samples that underwent identical manipulations was found positive for microbial contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Es ist auch ein Resinsystem kommerziell erhältlich, in das flüssige, aber auch feste Proben überführt werden können und nach einer Inkubation in diesem System in das mikrobiologische Testsystem überführt werden können (RESEP ® ). Mehrere Studien konnten bereits eine höhere Nachweisrate bei der mikrobiologischen Prüfung unter Verwendung dieses Systems zeigen [5,6].…”
Section: Inaktivierungunclassified